Epigenetic Reader Bromodomain-Containing Protein 4 in Aging-Related Vascular Pathologies and Diseases: Molecular Basis, Functional Relevance, and Clinical Potential - Xiaoxu Zheng; Kotryna Diktonaite; Hongyu Qiu (Biomolecules, 2023)
Aging is a key independent risk factor of various vascular diseases, for which the regulatory mechanisms remain largely unknown. Bromodomain-containing protein 4 (BRD4) is a member of the Bromodomain and Extra-Terminal domain (BET) family and is an epigenetic reader playing diverse roles in regulating transcriptional elongation, chromatin remodeling, DNA damage response, and alternative splicing in various cells and tissues. While BRD4 was initially recognized for its involvement in cancer progression, recent studies have revealed that the aberrant expression and impaired function of BRD4 were highly associated with aging-related vascular pathology, affecting multiple key biological processes in the vascular cells and tissues, providing new insights into the understanding of vascular pathophysiology and pathogenesis of vascular diseases. This review summarizes the recent advances in BRD4 biological function, and the progression of the studies related to BRD4 in aging-associated vascular pathologies and diseases, including atherosclerosis, aortic aneurism vascular neointima formation, pulmonary hypertension, and essential hypertension, providing updated information to advance our understanding of the epigenetic mechanisms in vascular diseases during aging and paving the way for future research and therapeutic approaches.